2017
DOI: 10.5194/acp-17-14119-2017
|View full text |Cite
|
Sign up to set email alerts
|

Long-path measurements of pollutants and micrometeorology over Highway 401 in Toronto

Abstract: Abstract. Traffic emissions contribute significantly to urban air pollution. Measurements were conducted over Highway 401 in Toronto, Canada, with a long-path Fourier transform infrared (FTIR) spectrometer combined with a suite of micrometeorological instruments to identify and quantify a range of air pollutants. Results were compared with simultaneous in situ observations at a roadside monitoring station, and with output from a special version of the operational Canadian air quality forecast model (GEM-MACH).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 131 publications
5
30
1
Order By: Relevance
“…The HCN mixing ratios measured in this study are 2 orders of magnitude lower than the mean HCN mixing ratios of 3.45 ± 3.43 ppbv (continuous sampling from a near-road location) and 1.57±0.33 ppbv (mobile measurements in heavy traffic) previously reported for Toronto . Long-path FTIR measurements of HCN (1 min time resolution) were made above the busy Highway 401 in Toronto concurrent with the present study (July-August 2015) (You et al, 2017). Consistent with our low HCN measurements, the authors found that HCN mixing ratios only spiked above the FTIR method detection limit of 3.2 ppbv on three occasions (isolated 1 min data points).…”
Section: Overview Of Mobile Pollutant Measurementssupporting
confidence: 88%
See 2 more Smart Citations
“…The HCN mixing ratios measured in this study are 2 orders of magnitude lower than the mean HCN mixing ratios of 3.45 ± 3.43 ppbv (continuous sampling from a near-road location) and 1.57±0.33 ppbv (mobile measurements in heavy traffic) previously reported for Toronto . Long-path FTIR measurements of HCN (1 min time resolution) were made above the busy Highway 401 in Toronto concurrent with the present study (July-August 2015) (You et al, 2017). Consistent with our low HCN measurements, the authors found that HCN mixing ratios only spiked above the FTIR method detection limit of 3.2 ppbv on three occasions (isolated 1 min data points).…”
Section: Overview Of Mobile Pollutant Measurementssupporting
confidence: 88%
“…The absolute incandescence and temperature of the BC particles are measured by collection optics and photomultipliers. After appro-priate calibration and analysis, these two parameters are used to determine the soot volume fraction, which is converted to a BC mass concentration with knowledge of the particle material density (ρ) and the absorption function (E m ), both of which are well established for BC (Coderre et al, 2011;Choi et al, 1994;Wu et al, 1997). An advantage of this technique is that it determines ensemble properties for all particles within the sample volume and so does not suffer from a particle size limitation; previous studies have shown that the HS-LII can detect laboratory-generated particles < 7 nm in diameter (Stirn et al, 2009).…”
Section: High-sensitivity Laser-induced Incandescence (Hs-lii) For Blmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR has high sensitivity, permitting the detection of changes in gas concentration at the ppb (parts per billion, volume concentration) level. Openpath FTIR have been applied to the online detection of trace gas emissions from forest fires [14] and soil during the spring thaw [15], and from traffic emissions along highways [16] and in harbors [17]. e identification of each component in the FTIR spectrum is crucial for accurate quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…excluding satellite and ground based total column measurements) are differential optical absorption spectroscopy (DOAS), typically employing the UV and visible spectral regions (Platt and Stutz, 2008), and open-path Fourier transform spectroscopy (OP-FTS) in the mid-infrared (e.g. Tuazon et al, 1978;Russwurm and Childers, 2002;Griffith and Jamie, 2006;Smith et al, 2011;Laubach et al, 2013;Flesch et al, 2016;You et al, 2017). While DOAS can operate over path lengths of several kilometres, suitable absorptions for accurate and precise measurements of CO 2 , CH 4 and other greenhouse gases are not available in the UV-visible spectrum.…”
Section: Introductionmentioning
confidence: 99%